THE USE OF SOCIAL CULTURE AND LANGUAGE IN LEARNING AMERICAN LITERATURE - Isnawaty Lydia Wantasen (Universitas Stikubank (UNISBANK) Semarang, 2009)
A work of literature is a reflection of events or phenomena in the society and expressed in several literary genre, such as drama, prose and poetry. It is also known that social environment plays an important role in creating the culture and this is inseparable from the role of language. As a means of communication, language expresses all these social events loaded with moral values. Learning social culture and language shall contribute to the horizon of knowledge. This paper tries to investigate the use of social culture and language in an attempt to learn American culture. Apart from the clear fact that there is a close relationship between language and culture, it should be noted that language is part of culture not the other way around. Therefore when learning a language, at the same time the students need to be equipped with the knowledge of culture. Most importantly, in learning literature, it involves learning the language and culture. Key words: social, culture, language, literature